THE ISSUE OF “CULTURAL AMNESIA” IN THE CONTEXT OF DIGITAL CULTURAL HERITAGE MANAGEMENT - M. Yu. Zakharov; I. E. Starovoytova; A. V. Shishkova (Вестник университета)
The issue of the dual impact of innovative technologies on the sphere of spiritual culture has been considered. On the one hand, the digitalization of cultural values gives hope for their longevity, compared with traditional storage methods. On the other hand, the preservation of cultural heritage is facing new, previously unmet difficulties: the life of digital documents is short due to constant technological improvement and the rapid obsolescence of technology; not all artifacts can be digitized; when knowledge is transmitted through the media, its reduction, vulgarization occurs; finally, the person is changing, for whose sake the preservation of the cultural heritage takes place. Generations possessing clip thinking will have to deal with the fragmented, unsystematic cultural heritage, which is fraught with real cultural amnesia. The new approaches to digital information management and, specifically, digital cultural heritage have been proposed in the article.